2016
DOI: 10.9790/487x-1810044349
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Financial Innovations On Performance Of Microfinance Institutions In Nakuru Town, Kenya

Abstract: Innovation is described as the process by which, firms master and implement design, and the production of goods and services that are new to them. Innovations generally assume different forms such as product innovations, marketing innovations, micro MFIS, location innovation, and research and development innovation. Financial innovations include institutional innovation, product innovation, and process innovation. These innovations have eased the way of doing business for financial institutions including micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 5 publications
5
15
0
Order By: Relevance
“…However, if leverage is measured from long-term debt, it has no effect on firm performance. These results are consistent with those from the previous study, showing a positive effect of debt capital on profitability (Waweru, 2016). This result provides evidence that rural banks in their operations emphasize the use of short-term debt in the form of savings, both ordinary savings and savings deposits from their customers.…”
Section: Effect Of Leverage On Roa and Roesupporting
confidence: 92%
“…However, if leverage is measured from long-term debt, it has no effect on firm performance. These results are consistent with those from the previous study, showing a positive effect of debt capital on profitability (Waweru, 2016). This result provides evidence that rural banks in their operations emphasize the use of short-term debt in the form of savings, both ordinary savings and savings deposits from their customers.…”
Section: Effect Of Leverage On Roa and Roesupporting
confidence: 92%
“…In the banking context, these results are consistent with the results of previous research studies (El-Masry, 2016;Siddik et al, 2017). In the context of microfinance, these results contradict to the results of previous studies, which have shown that debt capital has a positive effect on profitability (Waweru, 2016). The main effects of saving to total assets ratio (SA_TA), loans to total assets (LO_TA) and other debt to total assets (OD_TA) on ROA and ROE are shown in models 2 and 4.…”
Section: Main Effect Of Capital Structure On Performancesupporting
confidence: 75%
“…The study of Vishnu (2019) also shows that the capital structure has a significant impact on the financial performance of the banks in India. On the contrary, Waweru (2016) found that capital structure does not significantly influence the profitability of MFIs. Several studies in Indonesia have also shown similar results.…”
Section: Impact Of Capital Structure On Performancementioning
confidence: 86%
“…Therefore, financial performance of microfinance institutions has been the attention of researchers in the recent days. The experienced competition among commercial banks and telecommunication money transfer platform has led to micro-finance institutions change in market share and profitability such as MPESA (Okombo, 2015), therefore these bring innovation and the gap which can be closed by increase in liquidity which can be used to fund and facilitate the process according to the size of the micro-finance institutions. Most of the previous studies under this research addressed the characteristics that had an influence on the financial performance of microfinance institutions but did not indicate the moderating variable to bring out the relationship between the independent variable and dependent.…”
Section: Statement Of the Problemmentioning
confidence: 99%